Improvement of Dye Solar Cell Efficiency by Photoanode Posttreatment - Tanja Ivanovska; Zoran Saponjic; Marija Radoicic; Luca Ortolani; Vittorio Morandi; Giampiero Ruani (International Journal of Photoenergy)
The basic concept for efficiency improvement in dye-sensitized solar cells (DSSC) is limiting the electron-hole recombination. One way to approach the problem is to improve the photogenerated charge carriers lifetime and consequently reduce their recombination probability. We are reporting on a facile posttreatment of the mesoporous photoanode by using a colloidal solution of TiO2 nanoparticles. We have investigated the outcome of the different sintering temperature of the posttreated photoanodes on their morphology as well as on the conversion efficiency of the DSSC. The DSSCs composed of posttreated photoanodes at 450°C showed an increase in JSC and consequently an increase in efficiency of 10%. Investigations were made to determine the electron recombination via the electrolyte by the OCVD technique. We found that the posttreatment has the effect of reducing the surface trap states and thus increases the electron lifetime, which is responsible for the increase of the overall cell efficiency.